Assessment of antecedents for violence against doctors: a cross sectional study on health worker component - Panigrahi, Sunil Kumar; Satpathy, Parmeshwar; Majumdar, Sagarika; Pal, Anjali (International Journal Of Community Medicine And Public Health, 2020)
Background: The occupational safety and health administration considers physicians, nurses and other healthcare providers to be vulnerable and at a high risk of workplace violence. 75% of the doctors in India have been victims of violence at workplace. Methods: This was a hospital based cross sectional study among resident doctors in a tertiary care hospital of Maharashtra. Results: Among 137 residents interviewed, 81% of them faced verbal abuse in previous 1 year. In 57.6% of the cases the perpetrators of violence were the relatives of the patients. The most common place of harassment was the indoor patient wards followed by emergency/casualty department. Conclusions: Lifestyle factors such as quality of sleep pattern, addictions have associations with events of harassment among the resident doctors. There should be a comprehensive plan aimed at reducing the lifestyle risk factors of the physicians and allow them proper rest between duty hours.